Comparative Transcriptome Analysis in Taraxacum koksaghyz to Identify Genes that Determine Root Volume and Root Length - Wieghaus, Annika; Roelfs, Kai-Uwe; Twyman, Richard M.; Prüfer, Dirk; Schulze Gronover, Christian (Frontiers in Genetics, 2022)
The Russian dandelion (Taraxacum koksaghyz, family Asteraceae) produces large amounts of natural rubber in the laticifers of its roots. This species has been proposed as an alternative source of natural rubber to augment or partly replace the rubber tree (Hevea brasiliensis) but domestication would require genetic improvement to increase rubber yields and agronomic optimization to facilitate harvesting and processing. Optimization has focused thus far on the size and shape of the roots, the primary storage organ for natural rubber and inulin. However, the corresponding genetic factors are poorly understood. Here we describe the comparative transcriptomic analysis of root tissues from T. koksaghyz populations featuring different root sizes and shapes, aiming to identify differentially expressed genes correlating with root length or root diameter in the upper root and root tip. The resulting datasets included multiple candidate genes for each trait and root part. Three genes were tested by qRT-PCR in outdoor-grown plants with diverse root morphology, and the expression of two genes correlated with the appropriate root morphotype, confirming the effectiveness of our method. We evaluated the candidate genes to gain insight into their potential functions in root development. Such candidate genes could be suitable for marker-assisted breeding programs in the future.